Behaviour and Emotional Health of Adolescent Boys Engaged in Non-Suicidal Self-Injury - Salma Siddiqui; Sehar-un-Nisa Hassan (NUST Journal of Social Sciences and Humanities, 2021)
Non-suicidal self-injury (NSSI) among adolescents has become a rising concern worldwide and a risk factor for suicide. There is a noticeable rise in number of children who attempted or committed suicide in past few years in Pakistan. However, not much attention has been paid to identify and target risk factors. A preliminary survey was conducted to assess nature of risk factor for NSSI and significance of main study. Participants were 12-17 years old boys (N=104) from schools of Islamabad. The variables of interest were assessed through The Non-Suicidal Self-Injury Assessment Tool (NSSI-AT), Abbreviated Dysregulation Inventory (ADI), Depression Scale for Adolescents (DSA), Peer Relations Questionnaire (PRQ) and Strengths and Difficulties Questionnaire (SDQ). Findings revealed that 34.6% adolescent boys were engaged in NSSI. Participants who reported self-harm had significantly high levels of distress, conduct problems, emotional, and behavioral dysregulation. Findings manifest the need to identify significant risk factors of NSSI among adolescents.